Gaps in the vision to action process conducted in Zimbabwe - Murugani, Vongai Gillian; Freed, Sarah; Voss, Rachel; Chimonyo, Vimbayi Grace Petrova (CIMMYT, 2025)
The CGIAR initiative Transformational Agroecology across Food, Land and Water Systems operates in Zimbabwe’s Mbire and Murehwa districts with the objective of supporting a transition toward environmentally sustainable, productive, and socially just agri-food systems. As the initiative enters a transition year toward the Multifunctional Landscape Science Programme, this report critically reviews past and ongoing activities to assess their coherence with, and responsiveness to, community-defined visions and priorities. The analysis draws on qualitative evidence generated through systematic document review, fieldwork conducted in both districts, and key informant interviews with current and prospective participants, providing an integrated basis for strengthening alignment between project design, implementation, and local aspirations. Crucially, the assessment also examines the extent to which these community-defined visions and priorities are themselves suitable and robust entry points for the design and implementation of multifunctional landscape interventions. Key findings of the report include: • Most project activities align with farmers’ visions, though gaps remain in all five target areas. There is strong alignment with achieving high levels of crop and livestock production, but gaps in water access and understanding the gradual transition process need to be addressed. Activities align with increasing farmers’ access to functional markets, but issues like market information and overcoming quantity bottlenecks remain. Communities have adopted strategies to manage natural resources, but fires and deforestation persist, and wildlife coexistence in Mbire remains challenging. Communities have some exposure to participation initiatives but need training to enhance active community participation. Partner organisations address gender inequality and GBV, but changing attitudes requires community leader support and more collaboration amongst development actors. • The Iniiative's actions are based on two assumptions: knowledge and incentives drive behaviour change. The Behaviour Change Wheel supports these assumptions but highlights that behaviour change is a gradual process requiring time for farmers to test interventions. • The initiative identified 472 stakeholders critical to local food system transitions, grouped into four categories: community, development, governance, and private sector. Community and governance stakeholders were most active, while private sector and development actors were underrepresented. Despite limited engagement, private sector actors provided essential services like machinery, seed, and contract farming arrangements. Moving forward, the Initiative will engage more development and private sector actors to address market access, gender inequality, and GBV. The report's final section outlines output and impact indicators to measure progress toward V2A goals.